Systematic revision of the flatfish genus Peltorhamphus Günther, 1862 (Teleostei: Pleuronectiformes: Rhombosoleidae), including description of a new species from Southeastern New Zealand, with biological and ecological summaries for the species - Munroe, Thomas A. (Zootaxa, 2021)
The flatfish genus Peltorhamphus Günther, 1862 (Pleuronectiformes: Rhombosoleidae) and its constituent species are redescribed based on examination of 1885 specimens. Four species are considered valid: three previously described (P. novaezeelandiae Günther, 1862, P. latus James, 1972, and P. tenuis James, 1972) and P. kryptostomus n. sp., described herein. Peltorhamphus novaezeelandiae, P. latus, and P. tenuis have widespread distributions on soft sediments in shallow coastal and inner continental shelf waters off both islands of New Zealand. Peltorhamphus novaezeelandiae has also been reported at the Chatham Islands. Previous reports of P. novaezeelandiae from Norfolk Island are erroneous. Peltorhamphus kryptostomus n. sp. has the most restricted geographic distribution in shallow coastal waters of the Otago-Southland region along the southeastern coast of South Island. The four species of Peltorhamphus are morphologically similar and overlap in many traditional meristic and morphometric features rendering identifications difficult, especially of juveniles and earlier life-history stages. Furthermore, throughout New Zealand waters, as many as three of the species possibly occur sympatrically, while in inshore areas of southeastern South Island, all four species may occur in sympatry. Novel morphological characters discovered in this study, combined with traditional diagnostic characters were used to identify and diagnose the species. Peltorhamphus tenuis is the most distinctive of the four, differing from congeners in the following combination of characters: greater length of second ocular-side pectoral-fin ray; its higher numbers of dorsal- and anal-fin rays and total vertebrae; having a series of small scales (best developed in specimens >70 mm SL) on blind sides of dorsal- and anal-fin rays (scales absent in congeners); its elongate body; and ocular-side pigmentation. The other three species are more similar morphologically and have frequently been misidentified both in fish collections and in some previous literature on these fishes. Of these three, P. novaezeelandiae, the largest in the genus, is distinguished from congeners by the combination of: its large size (reaching 510 mm SL vs. ≤ 200 mm SL); rounded head shape; blind-side squamation; the second ocular-side pectoral-fin ray shorter than body depth; ontogenetic variation in interorbital width; greater distance (4–8 scales wide) between ventral margin of lower eye and dorsal (upper) margin of rostral hood above the mouth; and 2–6 fleshy, finger-like filaments on the inner anteroventral margin of the fleshy skinfold on the ocular-side lower jaw. Peltorhamphus latus differs from congeners by the combination of: its short (maximum 150 mm SL), relatively deep body and bluntly pointed snout; blind-side squamation; relatively long, robust gillrakers on first gill arch, with upper limb gillrakers long, but not usually overlapping tips of dorsalmost gillrakers on the lower limb; black pigment on entire roof of mouth; relatively large eyes and narrow interorbital width (without significant ontogenetic variation); short diagonal distance (usually 2–3 scales wide) between ventral margin of lower eye and dorsal (upper) margin of rostral hood above the mouth; and absence of finger-like filaments on the inner anteroventral margin of the fleshy skinfold on the ocular-side lower jaw. Peltorhamphus kryptostomus n. sp. is distinguished from congeners by the combination of: its deep body and smoothly rounded snout; blind-side squamation; long, robust gillrakers on the first gill arch, with some posterior gillrakers on the upper limb overlapping tips of the first and second dorsalmost gillrakers on the lower limb; black pigment on the entire roof of the mouth; relatively large eyes and relatively narrow interorbital width; wide distance between ventral margin of lower eye and upper margin of rostral hood (3–6, usually 4–5, scales wide); and 1–4 finger-like filaments on the inner anteroventral margin of the fleshy skinfold on the ocular-side lower jaw. Ecological and life-history information are summarized for each species, and a key to juveniles > 40 mm SL and adults is also provided. Re-assessment of the number of valid species of Peltorhamphus provides better understanding of species diversity within this genus and within the Rhombosoleidae, as well as that for the flatfish assemblage residing in New Zealand waters.